The effects of Ramadan intermittent fasting on football players and implications for domestic football leagues over the next decade: a systematic review - DeLang, M. D.; Salamh, P. A.; Chtourou, H.; Ben Saad, H.; Chamari, K. (Sports Medicine, 2022)
Background: The month of Ramadan will intersect with many football leagues` schedules over the next decade. Understanding the effects of Ramadan intermittent fasting (RIF) on physical performance is necessary to guide considerations for football players. Objective: The aim of this systematic review was to investigate the effects of RIF on physical factors in football players, and secondarily to consider the impact this may have on domestic club football leagues. Design: We conducted a systematic review using PRISMA guidelines. Data Sources: The online literature search utilized CINAHL (EBSCO), Cochrane Library, Embase.com, PubMed, and Scopus databases, and grey literature (all from database inception to May 2020). Study Selection Criteria: Inclusion criteria consisted of studies of football (soccer) players, data collected during and/or around Ramadan, with injury and/or performance data provided. Results: The search yielded 11,226 studies. Twenty-two studies were included following a review of titles, abstracts, and full texts. Studies included some iteration of before-Ramadan, during-Ramadan, and after-Ramadan data. Common measures observed included ratings of perceived exertion (n = 8), sprinting (n = 7), sleep (n = 7), peak heart rate (n = 6), jumping (n = 5), Yo-Yo intermittent recovery tests (n = 4), Wingate anaerobic test (n = 3), field-specific tests (n = 3), and injury rates (n = 2). Decreased physical performance was commonly observed during late afternoon/evening testing (before breaking the fast) and with high-intensity exercise. Conclusion: There appears to be a performance deficit related to RIF in Muslim football players. Studies should explore the effects of RIF on actual match demands. Due to the month of Ramadan emerging into league calendars, considerations should be made to accommodate Muslim football players who are intermittently fasting.